Pickled essence of Englishman: Thomas Lovell Beddoes—time to unearth a neglected poet?. Issue 1 (10th June 2004) - Bamforth, I
Abstract : Thomas Lovell Beddoes (1803–1849) was a doctor and intermittently brilliant poet whose explorations of "the florid Gothic in poetry" (his words) offer some of the most haunting, claustrophobic, and grotesque verse in the English language. Son of the pioneering Bristol scientist Thomas Beddoes and nephew of Maria Edgeworth the novelist, he stemmed, like Mary Shelley, author of the celebrated novel Frankenstein, from a line of influential freethinkers. This article situates Beddoes's work in the transition from the confident empiricism of the eighteenth century to the nineteenth century's imaginative reaction to social and intellectual life after the Napoleonic wars. Having spent most of his adult life in Germany (where he studied anatomy with the famous biologist Blumenbach) and latterly Switzerland, Beddoes engaged in radical politics, dabbled in the occult, and may even have encountered the German doctor/playwright Georg Büchner, whose career parallels his own. Beddoes hoped that by reading the body literally, in terms of its material structure, he would be able to bring about a revival of English theatre. Inevitable defeat led him to develop his signature form of abject irony. In view of the current interest in semiotics (a development of medical semiology), and the subterranean analogies in Beddoes's writing between the corpus and the corpse, his reputation ought to be rescued from the "critical pickle".